2017
DOI: 10.24840/2183-0606_005.002_0006
|View full text |Cite
|
Sign up to set email alerts
|

The culture of design thinking for innovation

Abstract: Design thinking has been adopted widely as a tool for innovation by companies and other organizations. However, statements by researchers and practitioners about what design thinking is are often seemingly conflicting with each other. This paper aims to improve our understanding of what design thinking for innovation is and under which conditions it can be implemented successfully. It discusses design thinking for innovation in the broader perspective of organizational culture. A framework of nine innovation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 28 publications
0
15
0
1
Order By: Relevance
“…For the purpose of a proper planning and design of a school, it is necessary to know first-hand the use that each space will have [37], and for this reason we should turn to participatory processes [34][35][36]. Particular efficiency is being demonstrated by the methodology of design thinking [13,[39][40][41].…”
Section: A Participatory Approachmentioning
confidence: 99%
“…For the purpose of a proper planning and design of a school, it is necessary to know first-hand the use that each space will have [37], and for this reason we should turn to participatory processes [34][35][36]. Particular efficiency is being demonstrated by the methodology of design thinking [13,[39][40][41].…”
Section: A Participatory Approachmentioning
confidence: 99%
“…Innovation and customer centricity are seen as central factors behind the implementation of design thinking. The induction of design competence into the management context has an effect on innovation and can lead to competitive advantages (Brown, 2008;Johansson-Sköldberg et al, 2013;Carlgren et al, 2016b;Prud'homme van Reine, 2017). Martin (2009, p.38) argued that design thinking "enables leaders to innovate along the path of the knowledge funnel (mystery, heuristic, algorithm) and the firms that master it can gain long-term business advantages."…”
Section: Designerly Thinking and Design Thinkingmentioning
confidence: 99%
“…In its essence, design thinking refers to a reflective practice, a problem-solving activity, and a practice-based activity toward design as the creation of meaning (Buchanan, 1992;Kimbell, 2011Kimbell, , 2012Johansson-Sköldberg et al, 2013;Carlgren et al, 2016a;2016b;Prud'homme van Reine, 2017). The idea is to bring design practice and competence into the managerial and/or learning context and find new ways to deal with a complex reality (Johansson-Sköldberg et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Research findings also suggest that DT allows to understand better the customers' needs [4,8,[11][12]16], although the benefits of this increased customer-centricity are not always clear. Furthermore, it has been shown that DT can be used in organizations not only for the development of innovative customer-facing products, but also to improve their own internal processes [14,16].…”
Section: Q2: Case Studies About Design Thinking Implementationmentioning
confidence: 99%
“…Existing literature has analyzed the challenges of DT implementation in enterprises and suggested some approaches to address them. The challenge most commonly mentioned when applying DT was the difficulty to handle the flexibility and unpredictability of DT [1][2]8,12], attributes which may defy the existing structures, roles and responsibilities, particularly in large and strictly rigid companies. Two distinct perspectives to address this challenge have emerged from the articles reviewed: (1) The structure and culture of enterprises clashes inevitably with DT, or (2) DT can co-exist with existing structures, practices or methods until it is assimilated.…”
Section: Q3: Identifying and Overcoming The Challenges Of Design Thinmentioning
confidence: 99%